Translation Trainees’ Self-censorship and its Pedagogical Implications: A Triangulated Investigation in Hong Kong - Wai-on, Law (TTR)

(untitled) (Association canadienne de traductologie, 2023)
Employing a triangulation method based on interviews, performance exercises, and think-aloud protocols (TAPs), this study probes the thought processes of ten Hong Kong translation trainees of diverse backgrounds to identify possible self-censorship during translation. The two English source texts for the performance exercise contained sensitive language or content with respect to sex and the trainees’ home country. A text containing mild criticism of Christianity was used as a control. It was found that most respondents were aware of the relationship between ideology and translation, and employed a semantically literal translation approach to render the ideological items in full. They took a broad range of factors into consideration, including translation purpose, text type, register, and target readership. Only one respondent self-censored his translation, while three others revealed their concerns about censorship during the TAP. The results show that the trainees share the same social habitus and highlight a need for ethics-awareness training in the translation curriculum. Given the current lack of such training as revealed by other surveys, recommendations for curriculum design are made. The influence of habitus on self-censorship could be further explored by comparing, for example, translation trainees and professional translators. The research methodology could also be replicated in other cultural and linguistic settings for a broader understanding of this topic.